Study on Mechanical Properties and Application of FRP Confined Concrete-Filled Steel Tube Columns - Fang, Yunpeng (Transactions on Engineering and Technology Research, 2024)
With the increasing demand for high performance and high durability materials in civil engineering, traditional structural materials such as concrete columns and steel columns face challenges. Concrete-filled steel tube (CFST) columns combine the advantages of both, but are susceptible to corrosion. This study focuses on the mechanical properties and application prospects of fiber reinforced polymer (FRP) confined CFST columns. Firstly, the effect of FRP confinement on the compressive strength, ductility and toughness, crack resistance and shear resistance of CFST columns is discussed. Secondly, through theoretical analysis, performance exploration and practical application cases, the broad application prospects of FRP confined CFST columns in high-rise buildings, bridge engineering and reinforcement are verified. The findings point to a new avenue for technical advancement in the field of civil engineering since the double confinement of FRP greatly increases the bearing capacity and stability of CFST columns. Finally, the study points out that the future needs to deepen the research on the interface bond performance, long-term durability and optimal design of FRP, steel pipe and concrete, so as to encourage the widespread use of FRP constraint technology in civil engineering and contribute to the creation of a smarter, safer, and more environmentally friendly future city.